Everything in moderation: The implementation of a quality initiative - Ewens, B.; Andrew, L.; Scott, Rowena (West Australian Network for Dissemination, 2014)
This paper describes the development and implementation of a standardised moderation process within the School of Nursing and Midwifery at Edith Cowan University in Western Australia. This quality improvement initiative was the result of collaboration between two nursing course coordinators and a Centre for Learning and Development academic. The school employs a large team of sessional tutors who provide marking support to the unit coordinators. The purpose of this initiative was to standardise the marking of assessments across this team and to enrich the quality of assessment. The process was informed by best available evidence and underpinned by university guidelines and policy. The process was implemented in 2013 and initial indications were that it was well received by academic staff. However, retrospective evaluation revealed low implementation rates by academic staff. Potential reasons for this lack of engagement have been postulated, however, a prospective study will be conducted in 2014 to determine the contributing factors in order to improve engagement with this process.